2008
DOI: 10.1080/08958370701864797
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation, Endothelial Dysfunction, and Activation in Clinically Healthy Children Exposed to Air Pollutants

Abstract: Mexico City children are chronically exposed to significant concentrations of air pollutants and exhibit chronic respiratory-tract inflammation. Epidemiological, controlled human exposures, laboratory-based animal models, and in vitro/in vivo studies have shown that inflammatory, endothelial dysfunction, and endothelial damage mediators are upregulated upon exposure to particulate matter (PM). Endothelial dysfunction is a critical event in cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
98
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(116 citation statements)
references
References 54 publications
5
98
1
2
Order By: Relevance
“…Over the last 20 years, exposure to fossil fuel combustion has attracted significant medical interest. Many studies have demonstrated that current levels of air pollutants contribute to cardiovascular and respiratory morbidity and mortality in adults and children (2,3,(12)(13)(14). We have analyzed air pollutant measurements in the Sao Paulo metropolitan area over the last 30 years, and observed that pollutant levels recorded at each station were highly correlated with one another.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Over the last 20 years, exposure to fossil fuel combustion has attracted significant medical interest. Many studies have demonstrated that current levels of air pollutants contribute to cardiovascular and respiratory morbidity and mortality in adults and children (2,3,(12)(13)(14). We have analyzed air pollutant measurements in the Sao Paulo metropolitan area over the last 30 years, and observed that pollutant levels recorded at each station were highly correlated with one another.…”
Section: Discussionmentioning
confidence: 95%
“…In large cities, these small particles are the most harmful to human health, as they can induce pulmonary inflammation and oxidative stress, which in turn may stimulate specific transcription factors, such as nuclear factor kB, activator protein 1, chemokines, and other serum proinflammatory mediators (12). Some studies have demonstrated that exposure to high concentrations of pollutants is associated with an increased level of serum inflammatory markers in children (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Siddique et al (2011) compared children living in the New Delhi (India) urban area with children living in rural areas and showed that ADHD was positively correlated with current PM 10 levels. Air pollutants may induce systematic inflammation, which could be a possible mechanism mediating these effects (Block & Calderon-Garciduenas, 2009;Calderon-Garciduenas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Other potential explanations are that the urban children were more frequently exposed to ambient air pollution including fine particles. This may have led to systemic increases in inflammatory mediators [35,36] and, in turn, to an increase in insulin resistance and the metabolic risk score. However, as our results are new and raise several new research questions, they should first be replicated in a further study focusing on the different aspects of the neighbourhood environment.…”
Section: Discussionmentioning
confidence: 99%